Physiology of static breath holding in elite apneists - Bain, A. R.; Drvis, I.; Dujic, Z.; MacLeod, D. B.; Ainslie, P. N. (Experimental Physiology, 2018)
Breath hold related activities have been performed for centuries, but only recently within the last 30 years has it emerged as an increasingly popular competitive sport. In apnea sport, people compete in disciplines relating to underwater distances or simply maximal breath hold duration - with the current (oxygen un-supplemented) static breath hold record at 11:35 min. Remarkably, many ultra-elite apneists are able to supress respiratory urges to the point where consciousness fundamentally limits a breath hold duration. Here, arterial oxygen saturations as low as 50% have been reported. In such cases, oxygen conservation to maintain cerebral functioning is critical, where responses ascribed to the mammalian dive reflex - e.g., sympathetically mediated peripheral vaconstriction, and vagally mediated bradycardia - are central. In defence of maintaining global cerebral oxygen delivery during prolonged breath holds, the cerebral blood flow may increase by 100% from resting values. Interestingly, near the termination of prolonged dry static breath holds, recent studies also indicate that reductions in the cerebral oxidative metabolism can occur, likely attributable to the extreme hypercapnia and irrespective of the hypoxemia. In this review we highlight and discuss the recent data on the cardiovascular, metabolic and particularly cerebrovascular function in competitive apneists performing maximal static breath holds. The physiological adaptation and maladaptation with regular breath hold training are also summarized, and future research areas in this unique physiological field are highlighted, in particular the need to better determine the potential long-term health impacts of extreme breath holding.